Effect of Swift Heavy Ion Irradiation on Dielectric Properties of Manganite Based Thin Films. (2018) - Gadani, Keval; Rathod, K.N.; Joshi, Zalak; Dhruv, Davit; Joshi, A.D.; Asokan, K.; Shah, N.A.; Solanki, P.S.
Abstract: In this communication, we report the results of the investigations on the structural, microstructural and electrical properties of Y0.95 Sr0.05 MnO3 (YSMO) thin films with 100 nm thickness grown on (100) single crystalline SrNb0.002 Ti0.998 O3 (SNTO) substrates using pulsed laser deposition (PLD) technique. YSMO films were irradiated using 100 MeV O +7 swift heavy ions (SHI) with different fluence using 15 UD Tandem Accelerator, IUAC, New Delhi facility. Structural investigations using θ – 2θ X – ray diffraction (XRD) reveal that all the films crystallize in single phasic nature. With increase in ion fluence, structural strain is found to increase upon the irradiation using lower fluence of 1 × 10 11 ions/cm 2 which can be ascribed to the irradiation induced creation of defects at the interface. Further increase in ion fluence up to 1×10 12 ions/cm 2 can create more defects resulting in the degradation in lattice structure and hence strain gets enhanced. For the higher ion fluence of 1×10 13 ions/cm 2, local annealing takes place at the interface which in turn results in the improved structural strain and recrystallization process. To study the surface morphology of the pristine and irradiated films, atomic force microscopy (AFM) measurement was performed. To understand the electrical properties of presently studied YSMO / SNTO pristine and irradiated films, frequency dependent dielectric behavior was studied. It is seen that dielectric constant increases upon irradiation using the fluence of 1 × 10 11 ions/cm 2 and 1 × 10 12 ions/cm 2 while gets suppressed for 1 × 10 13 ions/cm 2 fluence. Variation in dielectric behavior with different ion fluence has been discussed on the basic of lattice strain and universal dielectric response (UDR) model.